CYDONIA OBLONGA MILL. (ROSACEAE) AT THE PETER THE GREAT BOTANICAL GARDEN - G. A. Firsov; A. V. Volchanskaya; K. G. Tkachenko; N. E. Staroverov; A. Yu. Gryaznov (Труды по прикладной ботанике, генетике и селекции)
20th century, common quince was considered not winter-hardy enough for the environments of the North-West of Russia. Cydonia oblonga Mill. was for the first time mentioned in the Catalogues of the Peter the Great Botanical Garden in 1793. It has been always present in the Garden's modern collection since 1949. The first flowering of common quince was noted in the late 1970s (after 20 years of cultivation), and in 2014 the first fruiting was recorded (65-year-old plants). The study of the quality of seeds has shown that in St. Petersburg's conditions they develop and almost ripen. However, for the time being the quality of seeds is insufficient to obtain seed reproduction. To increase seed quality cross-pollination is necessary. In North-Western Russia, quince has never been regarded as promising even for amateur cultivation, but it may become promising in case of further warming of the climate. Common quince is highly ornamental during its flowering period. It blossoms from late April to early May.